Literature Review: Tinjauan Aspek Keamanan Dan Kerahasiaan Rekam Medis Di Ruang Filing - Winda Indri Anggraeni; Deasy Rosmala Dewi; Nanda Aula Rumana; Muniroh (Yayasan Literasi Sains Indonesia, 2022)
To maintain the security and confidentiality of patient medical records, a medical record storage room is required that meets the provisions in maintaining the security and confidentiality of medical records. This study aims to determine the security aspects in terms of physical, chemical and biological as well as the confidentiality aspects of medical records in the filing room. This study uses a literature review method with the PICO framework. Search articles using the Google Scholar database with keywords and Boolean operators in this study are